Comparison of the effect of sodium bicarbonate use on the performace of athletes and non-athletes - Ozmerdivenli, R.; Baysal, B.; Karacabey, K.; Saygin, O. (My University, 2004)
It is known that sodium bicarbonate (NaHCO3) is used by athletes before exercise to delay fatigue and improve performance based on the knowledge that it removes H+ ions from the body through the creation of a metabolic alkalosis state. In this study, the effects of 0.3 g/kg NaHCO3 given orally to athletes and non-athletes before a 600 m race were compared. The study included 20 sprinters involved in active sports and 20 non-athlete volunteers. The subjects were fed with the same diet on the study day, and three hours after their lunch meal they were made to warm up for 10 minutes after which their serum HCO3, pH and Hla levels before and after a 600 m race were determined. After resting for 48 hours 0.3 g/kg. NaHCO3 was given orally as a 500 ml fruit juice and thesame determinations made under thesame conditions 2 hours later. The results obtained were evaluated by the one way ANOVA and the student t tests. Statistical significance was established as (p< 0.01) and (p < 0.05). In the study, the time taken to complete race after the administration of NaHCO3 fell compared to that before its administration in the athletes. In the same way, the racing time in the non-athletes group showed a fall after the administration of NaHCO3. However, the fall was below the fall recorded in the athletes group. The level of HCO3 before the administration of NaHCO3 in the athletes was observed to be higher than after the administration of NaHCO3. In a similar manner, the increase was observed in the non-athletes group. The pH after the administration of NaHCO3 was found to be higher than that before its administration both before and after exrcising. A rise in the HLa levels was observed after exercising following the administration of NaHCO3' in the athletes. The differences in the other parameters apart from that in pH were not statistically significant (p< 0.01), (p< 0.05). In conclusion, it can be said that, use of NaHCO3 at doses low enough not to cause gastrointestinal disturbances (like nausea, vomiting, abdominal cramps, diarrhea, bleeding, pain and unpleasant taste) is one of the factors that positively affect anaerobic performance in athletes, but this effect is lower than that observed in individuals leading sedentary lives. © 2004 Taylor and Francis Group, LLC.